Soy protein/chitosan-based microsphere as Stable Biocompatible Vehicles of Oleanolic Acid: An Emerging Alternative Enabling the Quality Maintenance of Minimally Processed Produce. (March 2022) - Gao, Sunan; Yang, Mingyi; Luo, Zisheng; Ban, Zhaojun; Pan, Ya; Tu, Mengyun; Ma, Quan; Lin, Xingyu; Xu, Yanqun; Li, Li
Abstract: In this work, the soy protein/chitosan-based microsphere (SCM), as a stable biocompatible vehicle of oleanolic acid (OA), was constructed for the first time under acidic conditions, and OA was firstly used for quality maintenance of minimally processed products. The effect of soybean protein isolate/chitosan ratio, particle concentration and oil fraction on emulsion stability was studied. Additionally, the interfacial characteristics of SCM with and without loading OA were determined by cryo-SEM. Results demonstrated that the encapsulation efficiency of SCM embedded with 0.15% OA (SCM-OA0.15% ) rated up to 87.53% ± 2.23%, and SCM-OA showed smaller particle size, greater stability, and better liquid-state behavior, as well as the enhanced antibacterial and antioxidant properties in comparison to the control and SCM group. The minimally processed apples were used to evaluate the potential application of SCM-OA delivery system and it was evident that SCM-OA contributed to reducing weight loss, maintaining total phenol content and inhibiting color browning of minimally process apples. These findings shed new light on the emerging biocompatible vehicles of plant-derived bioactive substance. Graphical abstract: Image 1 Highlights: Biocompatible Pickering emulsions loaded with OA were constructed for the first time. Interfacial properties of prepared microspheres were detected by cryo-SEM for the first time. SCM-OA effectively contributed to the quality maintenance of minimally processed apples. OA Loading further enhanced the physicochemical properties of SCM biocompatible vehicles. Stability of SCM-OA system was illustrated and quantified by Turbiscan in real-time.